Transformation images: the photojournalism of the Bang Bang Club and the last days of the Apartheid regime, 1990-1994 - Gomes, Raquel Gryszczenko Alves (ODEERE, 2016)
This paper is an initial research effort focused on the Bang Bang Club - a group of four photojournalists who registered the political transition in South Africa between 1990 and 1994 Working between the final days of the apartheid regime and the first democratic elections held in the country, these photojournalists and their work offer an opportunity to reflect on the relations between the photographic register and political memory in South Africa. Keywords: South Africa, apartheid, photojournalism, memory.